Hindu-Muslim Cultural Syncretism, Mixed Heritage, and Inter-Faith Harmony: Some Pragmatic Observations from Eastern India - Hossain, Intekhab (Studies in interreligious dialogue, 2018)
A considerable number of Indian Muslims live in West Bengal, a state located in the eastern part of the Indian sub-continent, where they not only hold basic Islamic values but also share local traditions of the region i.e., the Bengali culture universal to both the Hindu and Muslim communities. They have been living together side by side in peace and harmony for centuries without any contradiction between the different religious spheres although the margins are sharply defined by their respective beliefs and practices. Nevertheless, there is inadequate information regarding the social matrix and cultural dynamics of Muslims in this territory due to lack of adequate anthropological and sociological pragmatic research studies at the micro-level. The present account is a modest attempt to examine the nature of continuity, modification, and change in various aspects of the socio-cultural life and practices of the Muslims which have emerged as a result of centuries-long association and culture contact with the Hindu-dominated cultural milieu. Emphasis has also been given to underline the different spheres of communal harmony persisting between the two major religious communities of this region. In order to produce this research manuscript numerous secondary data sources have been consulted. Moreover, the author's personal observations and findings through empirical field study have also been combined in an organized and systematic manner.